Effect of ball milling and solid solution treatment on the microstructure and interfacial behaviors of ZrMgMo3O12p/2024Al composites. Issue 10 (15th May 2023) - Yang, Junrui; Yin, Chaofan; Zhao, Yinggang; Dong, Binbin; Liu, Ming; Fang, Pu; Zhou, Hui; Liu, Zhongxia
Abstract: ZrMgMo3 O12 is a negative expansion material, while 2024Al alloy is a positive expansion material. The difference in thermal expansion coefficients between them will cause thermal mismatch stress at the interface in ZrMgMo3 O12p /2024Al composites. Therefore, the interface behaviors of ZrMgMo3 O12 –Al determine the properties of ZrMgMo3 O12p /2024Al composites to a great extent. The effects of ball milling and solid solution treatment on the microstructure and interface behaviors of 10 vol% ZrMgMo3 O12p /2024Al composites were studied to improve the reticular microstructure of ZrMgMo3 O12 distributed at the grain boundary of the α-Al matrix. The results showed that with increasing milling energy, the microstructure of the composites changed from reticular to equiaxed, and the distribution of ZrMgMo3 O12 reinforcements in the matrix was more uniform. The content and size of the primary phase Al2 Cu decreased with increasing solid solution treatment time. In addition, only ZrMgMo3 O12 –Al, Al2 Cu–Al12 Mo and Al–Al12 Mo interfaces can be observed, but it is difficult to observe the interfaces of ZrMgMo3 O12 –Al12 Mo in the composites milled for 12 h and solution treated for 24 h, which is related to the decomposition mechanism of ZrMgMo3 O12 . The decomposition mechanism is as follows: Al atoms from the α-Al matrix captured O atoms from ZrMgMo3 O12 to form Al2 O3 . ZrMgMo3 O12 simultaneously released Mo, Zr and Mg atoms. Mo atoms were enriched and nucleated in situ and precipitated with Al atoms to form the intermetallic compound Al12 Mo, while Zr and Mg atoms entered the α-Al matrix to form a solid solution.